Methodologies for assessment of building's energy efficiency and conservation: A policy-maker view - Aleksandra Novikova (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Recent global peer-review reports have concluded on importance of buildings in tacking the energy security and climate change challenges. To integrate the buildings energy efficiency into the policy agenda, significant research efforts have been recently done. More specifically, the public domain provides a bulk of literature on the application of buildings-related efficiency technologies and behavioural patterns, barriers to penetration of these practices, policies to overcome these barriers. From the policy-making perspective it is useful to understand how far our understanding of building energy efficiency goes and the approaches and methodologies are behind such assessment.
Keywords: 330; Buildings; energy efficiency potential; greenhouse gas mitigation; policy assessment; energy policy impact evaluation; sectoral efficiency targets